Algorithm of surgical tactics for the treatment of carpal tunnel syndrome - A.K. Rushay; Yu.S. Lisaychuk; I.V. Voyennyy (Medičnì Perspektivi, 2023)
Carpal tunnel syndrome is the most common of compression neuropathies and in the structure of upper limb tunnel syndromes. Surgical treatments are diverse and clarifications of the indications for the implementation of each of them will allow to individualize the behavior of the intervention. Purpose of work – clarify the determining factors for classical and advanced minimally invasive intervention in carpal tunnel syndrome; evaluate the effectiveness of such an approach. We observed 52 patients with carpal tunnel syndrome with unsuccessful conservative treatment; electroneuromyographic and ultrasound signs of gross changes in the structures of the carpal canal. There were 19 men and 33 women (36.5% and 63.5%, respectively). In 28 patients (group 1), surgical intervention was performed according to the classical technique from an incision of 5.0-5.5 cm. Surgical treatment in 24 patients was carried out from an access of up to 2.5 cm (minimally invasive intervention). They made up the 2nd group. The dynamics of the indicators of the Boston BCTQ questionnaire and the visual analogue scale indicated a greater severity of symptoms, functional and pain disorders of the hand after 4 weeks in the extended access group compared with the minimally invasive access group with similar indicators before the intervention. However, by 3 and 6 months, the results converge and practically do not differ. Similar good results indicate the correctness of the chosen tactics and the validity of an individual approach in determining the nature and scope of the intervention.